PENGARUH LINGKUNGAN KERJA, MOTIVASI, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN PURWOREJO - Safitri, Lindarizki; Hirawati, Heni (Transpublika Publisher, 2022)
Employee performance is a component to measure the success of employees in carrying out the work. The purpose of this study was to analyze and determine the effect of work environment, work motivation, and leadership style on employee performance at the Department of Communication and Information, Purworejo Regency. The population in this study were employees at the Communication and Information Office of Purworejo Regency with a sample of 30 people whose data could be through questionnaires and then processed using multiple linear regression data analysis methods on SPSS type 23 software to measure the effect of work environment, work motivation, and leadership style on employee performance in the Department of Communication and Information Purworejo Regency. Based on linear regression analysis, it is known that Work Environment (X1), Work Motivation (X2), and Leadership Style (X3) have no significant effect on Employee Performance (Y) with a sig. more than 0.05 and testing (R) 0.273 and coefficient of determination (R Square) of 0.075 with the results of the value of the regression coefficient on the Work Environment variable (X1) of 0.168 stating that every 1% of the value of the work environment, will improve performance 16.8 %. The value of the regression coefficient on the Work Motivation variable (X2) of -0.49 means that every 1% of the value of Work Motivation, will reduce performance by 4.9%. The value of the regression coefficient on the Leadership Style (X3) variable is -0.116 which means that every 1% the performance value will decrease by -1.16%.